2020
DOI: 10.1007/s10964-020-01298-8
|View full text |Cite
|
Sign up to set email alerts
|

Peers and Homophobic Attitudes in Adolescence: Examining Selection and Influence Processes in Friendships and Antipathies

Abstract: Homophobic attitudes and behavior are a widespread problem among adolescents, but what the role of peer relationships such as friendships and antipathies is in shaping these attitudes remains unclear. Therefore, this study examined to what extent homophobic attitudes are influenced by friends’ and foes’ homophobic attitudes, and whether homophobic attitudes serve as a selection criterion for the formation of friendships and antipathies. Participants came from three Dutch high schools across two waves (wave 1 N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…They found that friends significantly influenced each other’s attitudes over the 2-year study so that friends’ attitudes became more similar over time. Similar studies of friendship networks have provided evidence for the socialization of anti-immigrant sentiment (Hjerm et al, 2018), homophobic attitudes (la Roi et al, 2020; Poteat, 2007), and attitudes toward ethnic minorities (Zingora et al, 2020).…”
Section: How Friends Influence Individuals’ Outgroup Attitudesmentioning
confidence: 79%
“…They found that friends significantly influenced each other’s attitudes over the 2-year study so that friends’ attitudes became more similar over time. Similar studies of friendship networks have provided evidence for the socialization of anti-immigrant sentiment (Hjerm et al, 2018), homophobic attitudes (la Roi et al, 2020; Poteat, 2007), and attitudes toward ethnic minorities (Zingora et al, 2020).…”
Section: How Friends Influence Individuals’ Outgroup Attitudesmentioning
confidence: 79%
“…Research also has shown that adolescents tend to befriend peers with similar levels of religiosity (Cheadle and Schwadel 2012;Leszczensky and Pink 2020). By contrast, a recent study found no evidence that adolescents befriend peers with similar levels of homophobic attitudes (La Roi et al 2020). Finally, adolescents with ethnic prejudice have been shown to avoid befriending inter-ethnic peers (Binder et al 2009;Stark et al 2013).…”
Section: Attitude and Behavior Homophilymentioning
confidence: 99%
“…Peer influence is a social process by which a focal individual's behavior or attitudes are affected by peers acting as reference points for the individual within social networks (Montgomery et al, 2020;. Whether it is due to peer influence or selection homophily processes (the tendency for individuals to form friendships with others of similar characteristics and behaviors (Krupka et al, 2016;), research shows that adolescent smokers usually have more smoking friends, whilst non-smokers have more non-smoking friends (Liu et al, 2017;. This correlation between an individual's smoking and the smoking behaviors of their peers has been shown to differ according to cultural characteristics (i.e., to be stronger for adolescent samples drawn from collectivistic, versus individualistic, cultures) (Liu et al, 2017).…”
mentioning
confidence: 99%
“…This paper aims to explore the behavioral mechanisms underlying the influence of social norms on adolescent smoking and vaping by examining whether changes in the experimentally elicited norms measures over time are correlated amongst friendship cliques, and broadly within the larger school community (e.g., school classes and school year groups). Our statistical approach draws upon the work of Krupka et al (2016), who studied selection homophily and peer influence effects for university freshmen's economic preferences (and related self-report outcomes), and our study's power calculation was also based on the work of Krupka et al, to detect changes in these effects (Hunter et al, 2020). Specifically, we examine selection homophily processes using mixed-effects logistic regressions to investigate whether similarity with another pupil on the smoking and vaping outcomes increases the likelihood of nominating them as a friend (objective 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation